Bidimensional H‐Bond Network Promotes Structural Order and Electron Transport in BPyMPMs Molecular Semiconductor. Issue 3 (11th February 2021) - De Nicola, Antonio; Correa, Andrea; Giunchi, Andrea; Muccioli, Luca; D'Avino, Gabriele; Kido, Junji; Milano, Giuseppe
Abstract: The presence of a hydrogen bond (H‐Bond) network has been proved to impact significantly the efficiency of organic light‐emitting diode (OLED) devices by promoting molecular orientation and structural anisotropy in thin films. The design of specific compounds to control H‐Bond network formation in an amorphous material, and hence to improve OLED performances, is needed. A successful example is given by the bi‐pyridyl‐based family n‐type of organic semiconductors named BPyMPM. The experimental evidences demonstrate a surprisingly higher electron mobility in thin film composed of 4, 6‐bis(3, 5‐di(pyridine‐4‐yl)phenyl)‐2‐methylpyrimidine (B4PyMPM (B4)), which is almost two order of magnitude higher than mobility measured for very similar member of the family, 4, 6‐bis(3, 5‐di(pyridine‐2‐yl)phenyl)‐2‐methylpyrimidine (B2PyMPM (B2)). Herein, a comprehensive computational study is presented, wherein classical and ab initio methods are combined, to investigate the 2D H‐Bond network in B4 and B2 thin films. The results indicate that B4 forms a larger number of intermolecular C‐H···N H‐Bonds that promote a higher orientational and positional order in B4 films, and superior electron transport properties. Abstract : Surprisingly, higher electron mobility in the thin film of B4PyMPM (B4), two orders of magnitude higher than mobility measured for other components of the BPyMPM family, is experimentally found. The present computational study elucidates the molecular origin of that difference, arising in the higher hydrogen bonds formed by B4, which promote a higher orientational order P2 and electron transport properties.